2019
DOI: 10.3389/fpsyg.2019.00367
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion and Subjective Well-Being Mediate the Impact of Mindfulness on Balanced Time Perspective in Chinese College Students

Abstract: Balanced time perspective is associated with optimal social functioning and provides psychological benefits in times of stress. Previous studies have found that mindfulness is positively associated with balanced time perspective and might promote it. However, the mechanism through which mindfulness affects balanced time perspective remains unexplored. The purpose of the present study was to investigate the mediating role of self-compassion and subjective well-being in the relationship between mindfulness and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 79 publications
2
20
0
2
Order By: Relevance
“…Compassion has been discussed in the human relations literature over the years and involves elements of inner feelings towards others and sympathizing and relating with the pain of another person (Kanov et al, 2004). In organizational settings, compassion has been discussed as a feeling where someone is deeply concerned about avoiding other people's suffering, in order to ensure their well-being Ge, Wu, Li, & Zheng, 2019). Thus, compassion is an empathic response towards others and is different than other constructs such as voluntary behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Compassion has been discussed in the human relations literature over the years and involves elements of inner feelings towards others and sympathizing and relating with the pain of another person (Kanov et al, 2004). In organizational settings, compassion has been discussed as a feeling where someone is deeply concerned about avoiding other people's suffering, in order to ensure their well-being Ge, Wu, Li, & Zheng, 2019). Thus, compassion is an empathic response towards others and is different than other constructs such as voluntary behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PNTP is positively associated with neuroticism, 2 and anxiety, 1 but is negatively associated with emotional stability, 1 self-esteem, 3 and subjective wellbeing. 3,4 Although PNTP can affect routine cognitive and behavioral decisions, in general, the negative impact PNTP can have on one's life is controllable. However, some people with high PNTP are prone to engage in unhealthy behaviors that have a negative impact on their lives, such as excessive drinking or Internet addiction.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several recent studies have identified a negative association between dispositional mindfulness and PNTP. 3,4,11 People with high dispositional mindfulness generally display less PNTP. 12 Generally speaking, mindfulness is considered to be nonjudgmental acceptance of and nonreactive awareness to internal and external stimuli, including emotions, cognitions, and sensory input, as experienced in the present moment.…”
Section: Introductionmentioning
confidence: 99%
“…Researches have shown that mindfulness can improve the SWB of aged people ( Aliche and Onyishi, 2019 ), workplace employees ( Allen et al, 2017 ), and teachers ( Hwang et al, 2017 ). Several researchers have also confirmed that college students with a higher level of mindfulness have a higher level of SWB ( Bajaj and Pande, 2016 ; Ge et al, 2019 ). Although there exists considerable evidence indicating that mindfulness has a positive effect on SWB, there is limited research to explore the mechanisms behind this relationship.…”
Section: Introductionmentioning
confidence: 90%